Content Analysis of Cloudy Years Novel - Khaknejad, Jamileh; Mohammadzadeh, Maryam (Journal of History Culture and Art Research, 2017)
In this study, we analyze the content of the “Cloudy Years” novel in order to introduce Iranian fictional literature, which its numerous dimensions are still unclear. Findings show that the socialism and belief in social commitment as the primary function of art and literature have led Ali Ashraf Darvishian -contemporary popular and committed author- to follow them in most of his works in order to consider the meaning related contents and contexts in his stories that. The main subject of cloudy years is political struggle and in terms of the theme it can be investigated from several political, social and historical aspects.